1995
DOI: 10.1002/ajim.4700280208
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic and central nervous system effects of lead in female glass workers in china

Abstract: To clarify the effects of lead on autonomic and central nervous system functions, electrocardiographic R-R interval variability (CVRR) as well as visual and brainstem auditory evoked potentials (VEP and BAEP) were measured in 36 female workers exposed to lead (exposed group) and in 15 female textile workers (unexposed group). The C-CVLF, C-CVHF (two component CVs of the CVRR reflecting sympathetic and parasympathetic activities, respectively), and LF/HF ratio (indicator of sympatho-vagal balance) were also com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 34 publications
2
37
1
3
Order By: Relevance
“…30 In a study of lead-exposed workers, electrophysiological parameters showed a significant exposure-associated HRV depression, although not the anticipated delayed latencies of BAEP peaks. 24 This finding may suggest that changes in HRV could be an earlier effect than increased BAEP latencies. Another study of occupational lead exposure reported an association between lead-induced changes in HRV and peripheral nerve conduction.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…30 In a study of lead-exposed workers, electrophysiological parameters showed a significant exposure-associated HRV depression, although not the anticipated delayed latencies of BAEP peaks. 24 This finding may suggest that changes in HRV could be an earlier effect than increased BAEP latencies. Another study of occupational lead exposure reported an association between lead-induced changes in HRV and peripheral nerve conduction.…”
Section: Discussionmentioning
confidence: 94%
“…The paucity of information is perhaps not surprising, given the substantial age-dependency of the HRV parameters that might complicate interpretation of cross-sectional studies. Studies of adults with occupational exposure to neurotoxicants [21][22][23][24][25][26][27][28] clearly show that HRV may be affected by chemical exposures that damage the nervous system. However, effects on children would be difficult to predict from studies conducted in adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the paired data of the BPb level and outcome variable in each subject were scored using Paint software (Microsoft Co., U.S.A.) after scanning the figure. Finally, four more studies were selected [24][25][26][27] , and therefore publication bias cannot be avoided in this case.…”
Section: Data Sources and Extractionmentioning
confidence: 99%
“…These methods include nerve conduction velocities (NCVs) [5][6][7][8][9][10][11][12][13][14] , visual-, auditory-and somatosensory-evoked potentials (VEP, AEP, SSEP) [10][11][12][14][15][16][17][18] , event-related potential (ERP) 7,8,10,11,14,17) and computer-based posturography 6,7,10,11,[18][19][20][21][22][23][24] . For example, neorophysiological tests have been employed to detect and document subclinical changes before lead-exposed individuals develop overt symptoms and signs, thereby preventing acute and/or persistent neurological illness among populations exposed to lead 18) .…”
Section: Introductionmentioning
confidence: 99%